A new name for Maiestas viraktamathi Fletcher and Dai, preoccupied by Maiestas viraktamathi Zahniser, McKamey and Dmitriev - Fletcher, Murray J.; Dai, Wu (Zootaxa, 2019)
Fletcher and Dai (2018) described two new species of Maiestas Distant from Australia, one of which was named Maiestas viraktamathi. Unfortunately, this name has already been applied to a species by Zahniser et al. (2012).